mRNA capping - Shatkin, Aaron (Henry Stewart Talks, 2007)
Modification of mRNA 5' ends by addition of a m7G cap structure, Capping for viability, Conservation in yeast to humans, Structure of caps and capping enzymes, Mechanism of cap synthesis, Protein-protein interactions that link capping to events in transcription, transport and translation, siRNA knockdown experiments